Synthesis and Deblocking Investigations of Phenol Blocked Aliphatic Isocyanates and Their Application in the Development of Epoxy-Polyurethane Films - Rajendran, Karthi; Srinivasan, Vennila; Govindarajan, Sankar (Asian Journal of Chemistry, 2022)
Phenol blocked hexamethylenediisocyanate adducts and polyisocyanates were synthesized and their structure was validated by FTIR, 1H & 13C NMR spectroscopy, TGA, DSC and CO2 evolution techniques were used to evaluate the deblocking temperature of blocked isocyanates. Gel time studies of blocked isocyanates with terathane polyol and solubility study of blocked isocyanates with different polyols were conducted to demonstrate the structure-property correlation. Epoxy-polyurethane films were produced utilizing the blocked isocyanates reported in this work with epoxy resin and their structure was verified by ATR Spectroscopy. TGA, DSC, shore A hardness, tensile strength and flexural strength analysis were used to investigate the thermal and mechanical characteristics of these films. The findings of deblocking temperature and gel time revealed that unsubstituted phenol blocked isocyanates and polyisocyanates deblock at lower temperatures and cure for a shorter time period than substituted phenol blocked isocyanates. Thermal and mechanical characteristics of epoxy-polyurethane films based on blocked polyisocyanates are satisfactory.